Polyester film and method for producing the same
Patent Information
- Application Number
- JP2023148992
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
AI Technical Summary
【0010】 本発明によれば、内包する微小な異物が少なく、光学用フィルム、特にタッチスクリーン用の電極基材として用いられた際に、欠陥が少ないポリエステルフィルムを提供することができる。
Smart Images

Figure 2025042148000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester film having few foreign matters and a manufacturing method thereof, and more specifically to a polyester film suitable as an electrode substrate for a touch sensor, which has few foreign matters caused by minute modified resins, which are usually difficult to detect but are visible at the pattern boundaries when a patterned functional layer is formed on the film, and a manufacturing method thereof. [Background technology]
[0002] Thermoplastic resin films, especially biaxially oriented polyester films, have excellent mechanical properties, electrical properties, dimensional stability, transparency, chemical resistance, etc., and are therefore widely used in many applications such as magnetic recording materials, packaging materials, etc. In particular, in recent years, they have been used in various optical films, including display components for touch panels, liquid crystal display panels (LCDs), plasma display panels (PDPs), organic EL panels, smartphones, etc.
[0003] In particular, for smartphones, portable game consoles, tablet PCs, and in-vehicle information displays, which have seen an increase in demand in recent years, the display units are viewed from close range, and so the base film for the display units is required to have few scratches and foreign matter. In addition, as the display units of these devices become increasingly high-definition, the base film is also required to have high visibility (high transparency, high gloss, no color unevenness, etc.). In particular, when there are many extremely minute foreign matter in a small area, they scatter external light and appear as bright spots, so there is a strong desire to reduce such minute foreign matter in applications where these devices are used at close range to the line of sight.
[0004] In particular, in electrodes for touch screens, a patterned electrode layer may be formed on a base film, and the gentle and minute unevenness of the base film surface at the boundary of the patterned electrode layer is emphasized by the difference in refractive index and becomes more visible. In the case of minute internal defects caused by resin-modified substances contained in the base film, they are usually difficult to detect, but become visible after the electrode is formed, so there is an increasing demand for the establishment of an inspection method for the base film before processing and for base films with fewer defects.
[0005] Conventional measures against foreign matter during film production include methods to reduce foreign matter adhering to the film surface, such as cleanliness management of the production environment and removal methods using dust collectors and adhesive rolls, and methods to reduce foreign matter contained in the film by reducing the filter opening when filtering molten resin. However, the minute resin modification substances present inside the film described above cannot be removed by dust collectors or adhesive rolls, and are difficult to remove because they slip through the filter even during the filtration process of the molten resin, making it difficult to improve. In addition, during the film production process, the minute resin modification substances are transparent, and the deformation of the film surface caused by them is broad and the boundary is unclear, making it difficult to inspect them, and there was also a problem of distinguishing them from defects caused by other causes.
[0006] To solve these problems, Patent Document 1 proposes a method to reduce foreign matter by adjusting the size of the chips and washing the chips with water after heat treatment. Patent Document 2 proposes a method to improve adhesion of foreign matter caused by precipitation of solids from a coating liquid onto a bar through precision treatment of the coating liquid. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2007-136987 A [Patent Document 2] JP 2006-272676 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, the method of Patent Document 1 is effective in improving defects caused by resin alteration products with a high melting point, but has the problem that it is insufficient when the cause is a gelled product. Also, the method of Patent Document 2 is insufficient as a measure against minute internal foreign matter. The present invention aims to solve the above problems and provide a polyester film that contains few minute foreign matter and has few defects when used as an optical film, particularly an electrode substrate for a touch screen. [Means for solving the problem]
[0009] The present invention aims to solve the above problems. That is, the particle content is 0.007% by mass or less, the Δ haze after heating at 150°C for 30 minutes is 13.0% or more, and the number of elongated internal defects of 10 μm to 100 μm that can be seen when observing with a coaxial incident light microscope by focusing on the film surface and then shifting the focus 18 μm upward is 20 / 250 mm. 2 The following is the result. Effect of the Invention
[0010] According to the present invention, it is possible to provide a polyester film which contains a small amount of minute foreign matter and has few defects when used as an optical film, particularly as an electrode substrate for a touch screen. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The polyester film of the present invention has a particle content of 0.007% by mass or less, a Δ haze of 13.0% or more after heating at 150° C. for 30 minutes, and a number of elongated internal defects of 10 μm to 100 μm in size that can be seen when observed with a coaxial incident light microscope by focusing on the film surface and then shifting the focus 18 μm upward is 20 / 250 mm. 2The polyester film of the present invention will be described in detail below.
[0012] In the polyester film of the present invention, from the viewpoint of suitable use in optical applications, the Δ haze after heating at 150° C. for 30 minutes is 13.0% or more, and the number of elongated internal defects with a size of 10 μm to 100 μm, which are visible when observed with a coaxial incident light microscope after focusing on the film surface and then shifting the focus 18 μm upward, is 20 / 250 mm. 2 10 pieces / 250 mm or less, preferably 10 pieces / 250 mm 2 The following is the result.
[0013] Here, "size between 10μm and 100μm" means that when two points are taken on the periphery of the internal defect so that the distance between the two points is greatest, the distance between the two points is between 10μm and 100μm. "Long diameter" means that when the internal defect is enclosed in a rectangle so that its area is smallest, the length of the long side of the rectangle is 1.5 times or more the length of the short side. Long-shaped internal defects are likely to become defects that are visible during processing, so they require particular management.
[0014] The number of internal defects is 20 / 250mm 2 If the number of internal defects exceeds 0 / 250 mm, the number of visible defects will increase when the material is used in a display member such as a touch screen. There is no particular lower limit for the number of internal defects, and the smaller the number, the fewer defects there will be in the final product, which is preferable. 2 The method for identifying internal defects using a coaxial incident light microscope and for measuring the number of internal defects with a major axis of 10 μm or more and 100 μm or less will be described later. 2 As a method for achieving the above, for example, it is effective to control the shear rate in the compression section of the extrusion process using a single screw extruder and the heater temperature in the compression section within specific ranges.
[0015] In addition, the polyester film of the present invention preferably has a haze of 2.0% or less, more preferably 1.0% or less, so as not to significantly reduce the clarity of the image or the amount of light when used in an image display device such as a display. From the above viewpoint, the smaller the haze, the more preferable, and there is no particular restriction on the lower limit, but from the viewpoint of feasibility, it is 0.3%. The haze can be measured by a known haze meter in accordance with the old JIS K7105 (1981), and the details of the measurement method will be described later. As a method for making the haze of the polyester film 2.0% or less, for example, it is effective to not mix light-scattering particles, various additives, coarse polymerization catalyst residues, etc. into the polyester resin used.
[0016] When the polyester film contains a large amount of internal foreign matter, the internal foreign matter acts as a nucleus to easily generate crystals. Since these crystals block the precipitation of oligomers from within the polyester film, the precipitation of oligomers is suppressed when the amount of internal foreign matter increases. Since such phenomena are caused by a slight change in crystallinity, the change in crystallinity caused by internal foreign matter can be confirmed using the Δ haze after heating as an indicator. From the viewpoint of reducing internal foreign matter, the Δ haze of the polyester film of the present invention after heating at 150°C for 30 minutes is preferably 13.0% or more, more preferably 15.0% or more. The Δ haze of 13.0% or more means that the precipitation of oligomers due to heating is not suppressed because there is little internal foreign matter in the polyester film. Even when particles are added to the raw material, the size of the added particles does not affect the crystallization of the polyester film, so there is no adverse effect on the Δ haze after heating. The Δ haze after heating at 150° C. for 30 minutes can be determined from the haze measured using a known haze meter in accordance with old JIS K7105 (1981), and the details of the measurement method will be described later.
[0017] In the present invention, as a method for reducing the number of internal defects caused by minute elongated resin modified substances and making the Δ haze after heating at 150° C. for 30 minutes 13.0% or more, for example, a method for producing the polyester film of the present invention can be used. The method for producing the polyester film of the present invention will be described below.
[0018] The method for producing a polyester film of the present invention is characterized in that a polyester resin is melt-extruded using a single-screw extruder, and the shear rate in the compression section of the single-screw extruder is controlled in the range of 530.0 (1 / s) to 885.0 (1 / s) and the heater temperature in the compression section is controlled in the range of 290° C. to 320° C. In this case, it is more preferable to control the shear rate in the compression section to 750.0 (1 / s) to 870.0 (1 / s) and the heater temperature in the compression section to 295° C. to 310° C. The shear rate in the compression section can be adjusted by changing the resin pressure setting and discharge amount before the gear pump.
[0019] To identify and count internal defects, a coaxial incident light microscope was used to focus on the film surface, and the objective lens was then shifted upward by 18 μm or less. The internal defects were selected from among the foreign bodies with a white, blurred periphery and a major axis of 10 μm to 100 μm. 2 The number of defects per unit area is calculated by converting the number of defects per unit area. By shifting the focus slightly, the boundary around the resin modified product appears bright, making it easier to visually identify the finely dispersed modified product. The magnification of the microscope can be appropriately set within the range of 200 times to 400 times in order to observe the target defects with a size of 10 μm to 100 μm.
[0020] Since minute resin modification products are fluid, it is difficult to remove them by filtration, and it is important to control their generation during the melt extrusion process. As a result of extensive investigation, it was found that controlling the shear rate of the compression section and the heater temperature of the compression section within a specific range during the extrusion process using a single-screw extruder is effective in suppressing the generation of minute resin modification products. The filling rate of the molten resin in a single-screw extruder is higher than that of extruders with multiple axes such as a twin-screw extruder, and heat deterioration due to retention of the molten resin and the inclusion of vaporized deposits, which can be disadvantages, are less likely to occur.
[0021] In the polyester film manufacturing method of the present invention, the shear rate in the compression section is set to 885.0 (1 / s) or less, thereby suppressing the increase in resin temperature due to shear heat and reducing the generation of gel-like foreign matter due to thermal decomposition of the polyester resin, thereby reducing the number of internal defects to be observed. On the other hand, the production capacity is improved by setting the shear rate in the compression section to 530.0 (1 / s) or more.
[0022] Furthermore, by setting the heater temperature of the compression section to 320°C or less, excessive increases in the polyester resin temperature are suppressed, and the generation of gel-like foreign matter due to thermal decomposition is reduced, thereby reducing the number of internal defects in the observation object. On the other hand, by setting the heater temperature of the compression section to 290°C or more, the generation of defects due to unmelted polyester resin with a high melting point during heat treatment is reduced, and similarly the number of internal defects in the observation object can be reduced.
[0023] In the polyester film manufacturing method of the present invention, if the screw length of the single screw extruder is short, the production volume cannot be increased, but if it is long, the resin is likely to deteriorate. Therefore, from the viewpoint of achieving both the production volume and the reduction of the deterioration of the resin, the effective length L / D of the extruder (L: screw length, D: cylinder diameter) is preferably 20 to 40. In addition, if the screw diameter φ is thin, the production volume cannot be increased, and if it is too long, the loss during material change or trouble increases, so from the viewpoint of the production volume and the reduction of the loss during trouble, it is preferably 200 mm to 300 mm. Regarding the compression ratio, if it is low, the resin pressure will also be low and the extrusion volume will decrease, so the production volume cannot be increased, while if it is too high, the shear heat will increase, which may cause the deterioration of the retained resin. Therefore, the compression ratio is preferably 3 times to 5 times.
[0024] The polyester constituting the polyester film of the present invention is a general term for polymers in which the main bond in the main chain is an ester bond, and can be obtained by polycondensation reaction of a dicarboxylic acid component and a glycol component. Here, examples of the dicarboxylic acid component include aromatic dicarboxylic acids such as terephthalic acid, naphthalenedicarboxylic acid, isophthalic acid, diphenyldicarboxylic acid, diphenylsulfonedicarboxylic acid, diphenoxyethanedicarboxylic acid, 5-sodiumsulfonedicarboxylic acid, and phthalic acid, aliphatic dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, sebacic acid, dimer acid, maleic acid, and fumaric acid, alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid, and oxycarboxylic acids such as paraoxybenzoic acid.
[0025] Of these dicarboxylic acids, terephthalic acid and naphthalenedicarboxylic acid are preferably used from the viewpoints of heat resistance, stability and productivity, and it is more preferable that 80 mol % or more of the acid components constituting the polyester are terephthalic acid and / or naphthalenedicarboxylic acid. In particular, for applications requiring strict stability, it is preferable that 95 mol % or more of the acid components constituting the polyester are terephthalic acid and / or naphthalenedicarboxylic acid, because these have excellent properties as described above.
[0026] Examples of the glycol component include aliphatic glycols such as ethylene glycol, propanediol, butanediol, pentanediol, hexanediol, and neopentyl glycol; polyoxyalkylene glycols such as diethylene glycol, polyethylene glycol, and polypropylene glycol; alicyclic glycols such as cyclohexanedimethanol; and aromatic glycols such as bisphenol A and bisphenol S.
[0027] The intrinsic viscosity (measured in o-chlorophenol at 25°C according to JIS K 7367 (2000)) of the polyester constituting the polyester film of the present invention is preferably 0.40 to 1.20 dl / g, more preferably 0.50 to 0.80 dl / g, from the viewpoints of moldability and reduction of polymer degradation.
[0028] Various additives, such as antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, lubricants, pigments, dyes, organic or inorganic fine particles, fillers, antistatic agents, nucleating agents, crosslinking agents, etc., may be added to the polyester film of the present invention to such an extent that the properties of the film are not deteriorated.
[0029] The lubricant used in the present invention is not particularly limited and can be appropriately selected within a range that does not impair the properties of the polyester film. For example, inorganic particles such as colloidal silica, titanium oxide, aluminum oxide, zirconium oxide, calcium carbonate, carbon black, and zeolite particles, and organic particles such as acrylic particles, silicone particles, polyimide particles, "Teflon" (registered trademark) particles, crosslinked polyester particles, crosslinked polystyrene particles, crosslinked polymer particles, and core-shell particles can be used. These particles may be used alone or in combination of two or more kinds. The number average primary particle size of these particles (hereinafter, sometimes simply referred to as average primary particle size or particle size) is preferably within the range of 10 to 1100 nm. Here, the average primary particle size is the average particle size of primary particles defined in JIS H7008 (2002) as particles generated by the growth of a single crystal nucleus.
[0030] From the viewpoints of productivity, quality, and transparency, the polyester film of the present invention needs to have a particle content of 0.007% by mass or less. By adding particles, the friction coefficient of the polyester film surface can be reduced, and the occurrence of scratches caused by rolls in the production process can be reduced. On the other hand, particularly in the case of display member applications, if the particles contained in the polyester film are too many, the transparency decreases, making it impossible to use it as a display member. By making the particle content 0.007% by mass or less, the friction coefficient of the film surface can be reduced while maintaining the transparency of the film, which is preferable. If the particle content exceeds 0.007% by mass, the transparency may deteriorate and the film may not be suitable for use as a display member. The lower limit of the particle content is not particularly limited, and the lower the particle content, the better the transparency, which is preferable. That is, the lower limit of the particle content is 0% (in other words, the addition of particles is optional).
[0031] The polyester film of the present invention is preferably a biaxially oriented polyester film. The term "biaxially oriented" as used herein refers to a film that exhibits a biaxially oriented pattern in wide-angle X-ray diffraction. A biaxially oriented polyester film can generally be obtained by stretching an unstretched polyester sheet by about 2.5 to 5.0 times in each of the longitudinal and transverse directions of the sheet, and then subjecting the sheet to heat treatment to complete the crystal orientation. The polyester film may also be a laminated structure of two or more layers. The longitudinal direction refers to the direction in which the film runs during the manufacturing process, and the transverse direction refers to the direction perpendicular to the longitudinal direction within the film plane.
[0032] The thickness of the polyester film of the present invention is preferably 20 μm or more and 250 μm or less, more preferably 50 μm or more and 125 μm or less. By having a thickness of 20 μm or more, the rigidity of the polyester film is maintained, and it can be suitably used for displays. On the other hand, by having a thickness of 250 μm or less, an excessive increase in rigidity is suppressed, deterioration of flatness such as curling is suppressed, and handling during transportation and processing is improved.
[0033] The polyester film of the present invention may have a functional layer laminated on the surface thereof, which provides functions such as easy slippage and adhesion. The method for laminating the functional layer is not particularly limited, but a coating method is preferred in that a thin film layer can be uniformly formed. The coating method may be a so-called offline coating method in which a polyester film is unwound and a coating composition is applied and dried to obtain a coated film in a separate process from the polyester film production process, or a so-called in-line coating method in which a polyester resin is extruded by an extruder, and the coating is performed during the film production process in which the polyester resin is formed into a sheet shape to obtain a coated film in one go.
[0034] The slip layer of the present invention may contain known polyester, acrylic, urethane, epoxy, and other resins, either alone or in combination, in order to provide various functions such as retaining lubricant particles, improving adhesion to other functional layers, and sealing oligomers precipitated from the film. Furthermore, it may contain a melamine, oxazoline, or carbodiimide crosslinking agent.
[0035] Next, the method for producing the polyester film of the present invention will be described using biaxially oriented polyethylene terephthalate (hereinafter sometimes abbreviated as PET) as an example, but the present invention is not limited thereto.
[0036] PET pellets having an intrinsic viscosity of 0.50 to 0.80 dl / g that constitute the base layer are vacuum dried. The moisture content of the PET pellets after vacuum drying is preferably 150 ppm or less, more preferably 100 ppm or less. By controlling the moisture content within a specific range, it is possible to prevent the generation of resin denaturation products due to hydrolysis during melt extrusion, which is preferable.
[0037] Then, the PET pellets are fed into a single-screw extruder, and the PET pellets are mixed and melted at the shear rate of the compression section and the heater temperature of the compression section described above, and filtered through a filter with an average opening of 2 μm to 20 μm made by sintering and compressing stainless steel fibers and / or stainless steel powder. The molten PET is then extruded into a sheet from a T-shaped die, and wrapped around a mirror-finished casting drum with a surface temperature of 10 to 60°C using an electrostatic casting method, and cooled and solidified to produce a non-oriented film. Then, this non-oriented film is stretched 2.5 to 5.0 times in the longitudinal direction between rolls heated to 70 to 100°C. The non-oriented film is preferably heated with a temperature-adjusted preheating roll, and may be heated in combination with a radiation heater installed above and below.
[0038] At least one side of the uniaxially oriented film thus obtained is coated with a water-based coating agent containing lubricant particles as necessary. The coating method is not particularly limited, but a bar coating method using a metering wire bar is preferably used because the coating amount can be easily adjusted by adjusting the wire diameter.
[0039] Thereafter, the film coated with the aqueous coating agent is guided to a drying zone by holding both ends of the film in the width direction with clips, where the aqueous coating agent is dried and heated at a temperature of 70 to 150 ° C., and then continuously stretched in the width direction by 2.5 to 5.0 times in a stretching zone at 70 to 150 ° C. Then, the film stretched in the width direction is heat-treated in a heating zone at 200 to 240 ° C. for 5 to 40 seconds, and passed through a cooling zone at 100 to 200 ° C. to obtain a polyester film in which a coating layer is laminated on a substrate polyester film in which crystal orientation has been completed. During the above heat treatment to cooling process, a 3 to 12% relaxation treatment may be performed as necessary. Although the above example is a longitudinal and transverse sequential stretching, the biaxial stretching may be either a longitudinal and transverse sequential stretching or a simultaneous biaxial stretching, and after the longitudinal and transverse stretching, the film may be re-stretched in either the longitudinal or transverse direction (either the longitudinal direction or the transverse direction).
[0040] Thereafter, both ends of the obtained polyester film in the width direction are cut with a known slitter or the like and then wound up to obtain an intermediate product of the polyester film of the present invention. The intermediate product obtained is cut to a desired width using a known slitter or the like and wound around a cylindrical core to obtain a film roll of the polyester film of the present invention of a desired length.
[0041] The polyester film of the present invention is used for optical applications, which refer to applications that produce some effect by transmitting, reflecting, or absorbing light, such as display members for touch panels, liquid crystal display panels (LCDs), plasma display panels (PDPs), organic EL panels, smartphones, etc. EXAMPLES
[0042] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. Prior to describing each example, methods for measuring and evaluating various physical properties will be described.
[0043] (1) Shear rate v(1 / s) The shear rate v of the compression section of the single screw extruder was calculated using the following formula: The shear rate was calculated at the maximum point in the compression section. v = π × D × (N / 60) × (1 / h) Here, D is the cylinder diameter (mm), N is the screw rotation speed (rpm), and h is the tip clearance (mm).
[0044] (2) Number of internal defects in elongated shapes The measurement was performed using a Keyence VK-X100 (eyepiece 20x) as the measurement device, following the procedure below. First, a 10mm x 25mm area of the polyester film was marked, and the surface behind the marking was filled in with a black oil-based pen, and this was used as a sample. The sample was set in the measurement device, and after adjusting the focus, the objective lens (10x) was moved 18μm upward to observe the marked area, and the number of oblong shapes (rectangles with the long side length 1.5 times or more longer than the short side length) with a size of 10μm to 100μm was counted among defects with a blurred white edge around a black object. The size of the defects, including the edge, was measured using the length measurement function of the measurement device.
[0045] (3) Haze and ΔHaze The haze of the polyester film was measured using a haze meter (Suga Test Instruments HZ-V3) before and after heating for 30 minutes at 150°C. The Δhaze was calculated by subtracting the haze before heating from the haze after heating (reference standard: old JIS K7105 (1981)).
[0046] [Reference Example 1] Preparation of polyester resin (A) Under a nitrogen gas atmosphere, 88 mol parts of terephthalic acid as a dicarboxylic acid component, 12 mol parts of sodium 5-sulfoisophthalate, and 140 mol parts of ethylene glycol as a glycol component were charged into an ester exchange reactor, and 100 mol parts of tetrabutyl titanate (catalyst) was added to the dicarboxylic acid component per 1 million mol parts, and an esterification reaction was carried out at 200°C for 6 hours. Thereafter, the distillate was removed until the reaction product became transparent, and a polycondensation reaction was carried out under reduced pressure at 260°C to obtain polyethylene terephthalate with an intrinsic viscosity of 0.65 dl / g. This was designated as polyester resin (A).
[0047] [Reference Example 2] Preparation of polyester resin (B-1) Polyester resin (B-1) was obtained by adding calcium carbonate particles having an average particle size of 1.05 μm to polyester resin (A) so as to give a content of 1 mass %.
[0048] [Reference Example 3] Preparation of polyester resin (B-2) Crosslinked polystyrene particles having an average particle size of 0.3 μm were added to the polyester resin (A) so as to give a content of 2 mass % to obtain a polyester resin (B-2).
[0049] The intrinsic viscosity was measured at 25° C. using an Ostwald viscometer with orthochlorophenol as a solvent. The average particle size was measured by cutting the film into ultra-thin slices of about 100 to 800 nm in the thickness direction, staining them with ruthenic acid, and measuring a total of 100 particles at various locations at 100,000 times magnification using a transmission electron microscope (JEM-1200X manufactured by JEOL Ltd.) to determine the circle equivalent diameter from the area, and then averaging the results.
[0050] <Example 1> The polyester resin (A) was treated in a vacuum at 160°C for 5 hours, dried until the moisture content was 50 ppm, and then fed to a single-screw extruder (screw diameter: 250 mm, L / D: 28, compression ratio: 4 times). The single-screw extruder was used to perform melt extrusion under conditions of a shear rate of 864 (1 / s) in the compression section and a heater temperature of 295°C in the shear section. The molten polyester resin (A) was then filtered through a filter with an average opening of 5 μm made by sintering and compressing stainless steel fibers, and then through a filter with an average opening of 14 μm made by sintering stainless steel powder, and then extruded into a sheet from a T-shaped die, and wrapped around a mirror-finished casting drum with a surface temperature of 25°C using an electrostatic casting method, and cooled and solidified to obtain a non-oriented film. This unoriented film was preheated to 80°C using a preheating roll, and then heated to 95°C from above and below using a radiation heater while being stretched 3.5 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls. It was then cooled to 25°C using a cooling roll to obtain a uniaxially oriented film.
[0051] Next, the following water-based coating agent was applied to one surface of the uniaxially oriented film, and the coating thickness was measured to be 6 μm using a metering wire bar with a wire diameter of 0.1 mm (#4). (Water-based coating agent) A water-based coating agent containing the following components and having a concentration of 5.0 mass% calculated as the solid content of polyester resin (A) when the solid content of polyester resin (A) is 100 mass parts. Polyester resin (A): 100 parts by mass Melamine-based crosslinking agent ("Nicalac" (registered trademark) MW12LF, manufactured by Sanwa Chemical Co., Ltd.): 5 parts by mass (solid content equivalent) Colloidal silica having an average particle size of 140 nm: 1 part by mass.
[0052] Then, the width direction both ends of the uniaxially oriented film coated with the water-based coating agent were held by clips, and the uniaxially oriented film was transported to a tenter oven and dried and preheated at an atmospheric temperature of 120°C. It was then continuously stretched in the width direction at a ratio of 3.7 times in a 120°C stretching zone. The obtained biaxially oriented film was then heat-treated for 10 seconds in a 230°C heating zone, and then cooled from 230°C to 120°C while being subjected to a 5% relaxation treatment, and then cooled to 50°C. Then, the width direction both ends were removed by a slitter and wound up to obtain a biaxially oriented polyester film. The properties of the obtained biaxially oriented polyester film are shown in Table 1.
[0053] <Examples 2, 3, 5, Comparative Examples 1, 2, 4, 5> A biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the extrusion conditions and film thickness were as shown in Table 1. The evaluation results are shown in Table 1. The film thickness was adjusted by adjusting the extrusion and speed. In Example 2, the production capacity was inferior to other Examples due to a decrease in shear rate.
[0054] <Example 4, Comparative Example 3> The polyester resins (B-1) and (B-2) prepared in Reference Examples 2 and 3 were mixed in a ratio of 10:1 (mass ratio), and the resulting mixture was added to the polyester resin (A) so that the particle amount was 0.005 mass% (Example 4) and 0.009 mass% (Comparative Example 3) of the total. A polyester film was obtained in the same manner as in Example 1, except that the polyester resin mixture thus obtained was used as a raw material and the extrusion conditions were as shown in Table 1. The evaluation results are shown in Table 1.
[0055] [Table 1]
[0056] In the table, the particle amount is the particle amount excluding the coating layer. [Industrial Applicability]
[0057] The polyester film of the present invention contains few minute foreign matter. Due to the above-mentioned properties, the polyester film of the present invention can be suitably used as an optical film, in particular, as an electrode substrate for a touch screen.
Claims
1. The particle content is 0.007% by mass or less, the Δ haze after heating at 150°C for 30 minutes is 13.0% or more, and the number of elongated internal defects of 10 μm to 100 μm in size that can be seen when observing with a coaxial incident light microscope after focusing on the film surface and then shifting the focus 18 μm upward is 20 / 250 mm. 2 The following is a polyester film.
2. 2. The polyester film according to claim 1, having a haze of 2.0% or less.
3. 3. The polyester film according to claim 1, which is used for optical purposes.
4. A method for producing the polyester film according to claim 1 or 2, comprising the steps of: A method for producing a polyester film, comprising: melt-extruding a polyester resin using a single-screw extruder; and controlling a shear rate in a compression section of the single-screw extruder within a range of 530.0 (1 / s) or more and 885.0 (1 / s) or less, and controlling a heater temperature in the compression section within a range of 290°C or more and 320°C or less.
Citation Information
Patent Citations
Laminated thermoplastic resin film roll and its manufacturing method
JP2006272676A
Polyester film for display
JP2007136987A
Cited By
Light source apparatus and projector
EP4811034A1